Identification of bacteria in total mixed ration silage produced with and without crop silage as an ingredient. (26th June 2014) - Nishino, Naoki; Ogata, Yu; Han, Hongyan; Yamamoto, Yasunari
Abstract As a forage source for total mixed ration (TMR) silage production, locally produced crop silage is now used in addition to imported hay. This type of TMR ensiling is regarded as a two‐step fermentation process; hence, a survey was carried out to determine whether the bacteria in crop silage affect the subsequent TMR ensiling. Fermentation product contents and bacterial community were determined for TMR silage and its ingredient silages collected in August, October and November. August product contained corn, sorghum and Italian ryegrass silages, October product had wheat silage exclusively and November product did not include any crop silages. Acetic acid, lactic acid, 2, 3‐butanediol and ethanol were predominant fermentation products in corn, sorghum, Italian ryegrass and wheat silages, respectively. Robust lactic acid fermentation was seen in TMR silage, even if acetate‐type and alcohol‐type silages were mixed as ingredients. The finding that bacterial community of the TMR silage appeared unrelated to those of ingredient silage supported this. Silages of various fermentation types can therefore be formulated without interfering with lactate‐type fermentation in TMR silage.